2013
DOI: 10.4028/www.scientific.net/amr.864-867.1767
|View full text |Cite
|
Sign up to set email alerts
|

Research on Scale Inhibition of Green Scale Inhibitors Used in the Industrial Recycling Cooling System with Reclaimed Wastewater

Abstract: The reclaimed water of domestic sewage reused in recycling cooling system has been widely spread and applied. Chemical scale inhibitors are the most economic and effective measures to prevent condensers and circulating pipes from scaling currently. Green scale inhibitor are highly regarded for their non-toxicity, phosphate-free, reproducibility and biodegradability. The paper selects two kinds of new green scale inhibitors used in the recycling cooling water of Beijing Thermoelectric Plant. By the measuring th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…In their study, Popov et al (2016) and Yue et al (2014) showed PESA scale inhibitor performance was superior to PASP. Therefore, PESA may be used as an alternative to PASP in anti-scaling operation (S. Kumar et al 2018;Popov et al 2016;Yue et al 2014) (Fig. 4).…”
Section: Polyepoxysuccinic Acid (Pesa)mentioning
confidence: 93%
See 1 more Smart Citation
“…In their study, Popov et al (2016) and Yue et al (2014) showed PESA scale inhibitor performance was superior to PASP. Therefore, PESA may be used as an alternative to PASP in anti-scaling operation (S. Kumar et al 2018;Popov et al 2016;Yue et al 2014) (Fig. 4).…”
Section: Polyepoxysuccinic Acid (Pesa)mentioning
confidence: 93%
“…Additionally, PESA has the strong chelating and dispersing abilities of the presence of carboxylic groups along its main molecule chain (Huang et al 2019). In their study, Popov et al (2016) and Yue et al (2014) showed PESA scale inhibitor performance was superior to PASP. Therefore, PESA may be used as an alternative to PASP in anti-scaling operation (S. Kumar et al 2018;Popov et al 2016;Yue et al 2014) (Fig.…”
Section: Polyepoxysuccinic Acid (Pesa)mentioning
confidence: 97%
“…In the same time these phosphorous compounds usually lead to water pollution and eutrophication, killing a large number of aquatic organisms. [40][41][42] Thus inducing the environment-friendly scale inhibitors like biodegradable polyaspartic acid [43][44][45] and polyepoxysuccinic acid 46,47 has been paid more and more attention. However, it is pointed that most degradable polymers employed in experiments only reach gratifying efficiency through high inhibitor concentration and low ambient temperature, 48 hardly fulfilling broader applications.…”
Section: Introductionmentioning
confidence: 99%